A feedback circuit comprising EHD1 and 14-3-3ζ sustains β-catenin/c-Myc-mediated aerobic glycolysis and proliferation in non-small cell lung cancer. (1st November 2021) - Huang, Jian; Tian, Fanglin; Song, Ying; Cao, Mengru; Yan, Shi; Lan, Xiuwen; Cui, Yimeng; Cui, Yaowen; Cui, Yue; Jia, Dexin; Cai, Li; Xing, Ying; et al.
Abstract: Mammalian Eps15 homology domain 1 (EHD1) participates in the development of non-small cell lung cancer (NSCLC). However, its role in mediating aerobic glycolysis remains unclear. Herein, microarray analysis revealed that EHD1 expression was significantly correlated with the glycolysis/gluconeogenesis pathway. Clinically, EHD1 expression was positively correlated with the maximum standard uptake value (SUVmax) in 18 F-FDG PET/CT scans. Additionally, EHD1 knockdown inhibited aerobic glycolysis and proliferation in vitro and in vivo. Furthermore, Wnt/β-catenin signaling was identified as a critical EHD1-regulated pathway. Co-IP, native gel electrophoresis, and immunoblotting showed that EHD1 contributed to 14-3-3 dimerization via 14-3-3ζ and subsequent activation of β-catenin/c-Myc signaling. Analysis of the EHD1 regulatory region via ENCODE revealed the potential for c-Myc recruitment, leading to transcriptional activation of EHD1 and formation of an EHD1/14-3-3ζ/β-catenin/c-Myc positive feedback circuit. Notably, blocking this circuit with a Wnt/β-catenin inhibitor dramatically inhibited tumor growth in vivo. The positive correlations among EHD1, 14-3-3ζ, c-Myc, and LDHA were further confirmed in NSCLC tissues. Collectively, our study demonstrated that EHD1 activates a 14-3-3ζ/β-catenin/c-Myc regulatory circuit that synergistically promotes aerobic glycolysis and may constitute a promising therapeutic target for NSCLC. Highlights: High EHD1 levels correlate with aerobic glycolysis and NSCLC proliferation in vitro and in vivo. EHD1 modulates 14-3-3 dimerization via 14-3-3ζ,  thereby activating 14-3-3ζ/β-catenin/c-Myc signaling. c-Myc-mediated transcriptional activation of EHD1 modulates aerobic glycolysis via forming a positive feedback circuit. EHD1 overexpression and increased 14-3-3ζ, c-Myc levels predict unfavorable prognosis in clinical NSCLC specimens. Blocking the EHD1/14-3-3ζ/β-catenin/c-Myc circuit constitutes a potential treatment strategy for patients with NSCLC.